Effect of drought stress and potassium foliar application on seed yield and seed germination characteristics of three wheat (Triticum aestivum L.) cultivars. - عباس زارعیان; آیدین حمیدی; حسین حیدری شریف آباد; قربان نورمحمدی; سید علی طباطبایی (علوم و فناوری بذر ایران)
In order to evaluate the effect of drought stress and potassium foliar application on seed yield and seed germination characteristics of three wheat (Triticum aestivum L.) cultivars, an experiment was conducted in 2011-2012 at two locates, 1. Seed and Plant Certification and Registration Research Institute (SPCRI), Karaj- Iran 2. Agricultural and Natural Resources Research Center of Yazd-Iran. The experiment was carried out using a split plot factorial based on a randomized complete blocks design with three replications. The water treatments included three irrigation regimes; normal, mild stress (warer withhold at the grain filling phase) and severe stress (water withhold at the ear emergence phase); potassium foliar treatments included, 0, 1.5% and 3.0% K2O applications and three wheat cultivars (Marvdasht, Pishtaz and WS-82-9).      Result showed that reaction of cultivars at two locates for seed yield was different under drought stress conditions. High and lowseed yield were producedwith WS-82-9 at Karaj under normal water use (9310 kg ha-1)and with Marvdasht cultivar at Yazd under sever drought stress (2220 kg ha-1), respectively. Seed weight and seed yieldshowed significantdecreases by increasing drought stress. The mentioned traits showed significantincreases by spraying of K2O and it was more at Yazd area under severe drought stress, because of more unfavorable condition. Spraying wheat plants with 3.0%K2O produced the highest value of seed yield (7321.9 kg ha-1); while control treatment (without potassium foliar application) at Yazd gave the lowest value of this character.     Significant interaction of location× drought stress× cultivar on seed wastes showed that reaction of cultivars at two places was different under drought stress conditions, so that minimum and maximum seed wastes were observedin WS-82-9 at Karaj under normal irrigation (%2.26)and in Marvdasht cultivar at Yazd under severe drought stress (%54.76), respectively.Results revealed that high and lowseed wastes were observedunder no application of potassium (22.14%)and withspraying 3.0 % K2O (13.99%), respectively.    Seed germination percentage before and after seed cleaning showed that seed cleaning had important role on  improvement of seed quality, in a way that drought stress had significant influence on seed germination percentage before seed cleaning, but drought stress had no significant influence on seed germination percentage and  mean germination time after seed cleaning.